Pengungkapan Corporate Social Responsibility dan Kinerja Keuangan Perusahaan Manufaktur Yang Terdaftar di BEI - Ridho, Khayyit Khalil; Effendy, Lukman; Hudaya, Robith (E-Jurnal Akuntansi, 2022)
CSR is basically very important to be applied to companies. The company's CSR activities will have a positive impact because companies that implement CSR activities will be able to attract the attention of consumers so that they can influence the company's image to consumers. The aim of the study is to determine the effect of CSR on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) by using ROA, ROE, and NPM as a proxy for financial performance. The method used to select the sample was purposive sampling, with a total sample of 131 manufacturing companies. The analysis used is simple linear regression. The results of the study are that CSR has a significant positive effect on ROA and ROE, but CSR has no effect on NPM. Keywords: Corporate Social Responsibility (CSR); Return on Asset (ROA); Return on Equity (ROE); Net Profit Margin (NPM)